2019
DOI: 10.1111/psyp.13317
|View full text |Cite
|
Sign up to set email alerts
|

Syllables constitute proximate units for Mandarin speakers: Electrophysiological evidence from a masked priming task

Abstract: Languages may differ regarding the primary mental unit of phonological encoding in spoken production, with models of speakers of Indo‐European languages generally assuming a central role for phonemes, but spoken Chinese production potentially attributing a more prominent role to syllables. In the present study, native Mandarin Chinese speakers named objects that were preceded by briefly presented and masked prime words, which were form related and either matched or mismatched concerning their syllabic structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 66 publications
2
15
0
Order By: Relevance
“…The present findings of theta modulation by WF invites a question of whether the syllable‐chunking mechanism found in speech perception also played, more or less, a role in the process of outputting monosyllabic orthographic codes. On one hand, a line of evidence found that access to orthographic codes depends on prior activation of phonological codes (e.g., Bonin, Peereman, et al., 2001; Qu et al., 2011), whose proximate unit are syllables in the case of Chinese characters (Cai et al., 2020; Chen & Chen, 2013; Zhang & Damian, 2019). And theta oscillation has been associated with syllable retrieval in Chinese spoken production (Jiang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The present findings of theta modulation by WF invites a question of whether the syllable‐chunking mechanism found in speech perception also played, more or less, a role in the process of outputting monosyllabic orthographic codes. On one hand, a line of evidence found that access to orthographic codes depends on prior activation of phonological codes (e.g., Bonin, Peereman, et al., 2001; Qu et al., 2011), whose proximate unit are syllables in the case of Chinese characters (Cai et al., 2020; Chen & Chen, 2013; Zhang & Damian, 2019). And theta oscillation has been associated with syllable retrieval in Chinese spoken production (Jiang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, however, evidence has mounted for cross-linguistic differences. Evidence from error analyses in Mandarin Chinese 8–10 , and studies implementing priming paradigms in Mandarin 1117 , and Japanese 18,19 , showed a lack of segmental processing, motivating the claim that the first likely phonological unit for retrieval, called the ‘proximate unit’, is syllabic in Mandarin, moraic in Japanese and segmental in Dutch, English and French.…”
Section: Introductionmentioning
confidence: 99%
“…One event-related potential (ERP) study replicated null effects of segmental priming in behavior, but did show segmental priming in ERPs (Qu, Damian, & Kazanina, 2012), while other ERP studies have reinforced the idea that syllables are a salient planning unit (Wang, Wong, Wang, and Chen (2017); A. W.-K. Wong, Chiu, Wang, Wong, and Chen (2018). Recent work suggests ERP indices for both syllable and segment retrieval are observable, with syllable-related components occurring prior to phoneme-related components in time (Qu et al, 2012;Zhang & Damian, 2019).…”
Section: Tone Interactions With 'Proximate Units' In Chinese Speech Pmentioning
confidence: 97%